2002
DOI: 10.1152/japplphysiol.00939.2001
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation by central command during actual and imagined handgrip under hypnosis

Abstract: The purpose was to compare patterns of brain activation during imagined handgrip exercise and identify cerebral cortical structures participating in "central" cardiovascular regulation. Subjects screened for hypnotizability, five with higher (HH) and four with lower hypnotizability (LH) scores, were tested under two conditions involving 3 min of 1) static handgrip exercise (HG) at 30% of maximal voluntary contraction (MVC) and 2) imagined HG (I-HG) at 30% MVC. Force (kg), forearm integrated electromyography, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
151
0
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 40 publications
4
151
0
7
Order By: Relevance
“…For instance, the DLPFC is an important brain region governing human cognition (see Duncan et al 2000 for review) and connects mono-and multi-synaptically with paralimbic CAN regions (Petrides 2005). Hence, the DLPFC may influence outflow commensurate to perceived grip task effort in a similar manner as was found for the ACC in a SPECT study which used hypnotism to suggest a perceived grip task (Williamson et al 2002).…”
Section: Discussionmentioning
confidence: 91%
“…For instance, the DLPFC is an important brain region governing human cognition (see Duncan et al 2000 for review) and connects mono-and multi-synaptically with paralimbic CAN regions (Petrides 2005). Hence, the DLPFC may influence outflow commensurate to perceived grip task effort in a similar manner as was found for the ACC in a SPECT study which used hypnotism to suggest a perceived grip task (Williamson et al 2002).…”
Section: Discussionmentioning
confidence: 91%
“…Heart rate (HR) and stroke volume are increased during rhythmic or dynamic exercise, which in turn produces an increase in cardiac output (8,25,27,44). HR, ventilatory rate, and arterial blood pressure (AP) are also increased during mental simulation of motor action without any actual contraction (5,45) and during attempted handgrip exercise under partial or total neuromuscular blockade (10,36), suggesting that the cardiac adaptation during exercise is a neurogenic response via the autonomic nervous system partly due to a signal descending from the higher central nervous system. When such autonomic regulation is lacking in heart transplant recipients or cardiac denervated dogs, the responses of HR and cardiac output to dynamic exercise are diminished and slowed down despite a compensatory rise in stroke volume (2,7,39).…”
mentioning
confidence: 99%
“…Therefore, the findings in the present study not only support the above concept (Amman et al 2013) but also suggest that effort-mediated ventilatory response during fatiguing IE cannot be explained by the conventional framework of central command that drives breathing via neural mechanisms consisting of parallel activation of motor and respiratory centers (Goodwin et al 1972;Heigenhauser et al 1983;Krogh and Lindhard 1913;Marcora et al 2008). Recent studies (Decety et al 1991;Thornton et al 2001;Williamson et al 2002Williamson et al , 2006Yunoki et al 2009) using a cognitive approach to dissociate peripheral neural signals from central command have suggested that central command-mediated response does not necessarily require parallel activation of central motor command. Thornton et al (2001) showed by using positron emission tomography (PET) that breathing during imagination of effortful exercise was increased with significant activations of the dorsolateral prefrontal cortex, supplementary motor areas, premotor area, and cerebellum.…”
Section: Discussionmentioning
confidence: 99%
“…Thornton et al (2001) showed by using positron emission tomography (PET) that breathing during imagination of effortful exercise was increased with significant activations of the dorsolateral prefrontal cortex, supplementary motor areas, premotor area, and cerebellum. Likewise, Williamson et al (2002) localized the insular and anterior cingulate cortices as important brain sites related to cardiovascular response induced by imagined handgrip exercise with effort sense. Although we cannot verify the neuroanatomical structure, our results suggest that effort-mediated hyperventilatory response to IE does not require an increase in central motor command from the primary motor cortex to exercising muscle.…”
Section: Discussionmentioning
confidence: 99%